Enhanced spin-orbit coupling in an epsilon-near-zero material - Eismann, Jörg; Ackermann, Lisa; Kantor, Brian; Nechayev, Sergey; Alam, M. Zahirul; Fickler, Robert; Boyd, Robert W.; Banzer, Peter (Optica, 2022)
Light can carry both spin and orbital angular momentum. While it is known that a nonparaxial circularly polarized beam couples the spin angular momentum to orbital angular momentum, this phenomenon does not hold upon col-limation of the field. With the rising interest in epsilon-near-zero photonics, integral ingredients to this field are the beam-shaping capabilities of such a regime. In this work, it is experimentally shown that a permanent conversion of spin-to-orbital angular momentum arises naturally from an incident circularly polarized field on an isotropic inter-face due to the asymmetry in the Fresnel coefficients. More significantly, the conversion efficiency can be substantially enhanced in the presence of an epsilon-near-zero film due to the unique Fresnel properties exhibited in such a regime. It is further shown that the conversion efficiency scales with the nonparaxiality of the incident field. Our study showcases the intriguing phenomena resulting from the combination of concepts as old as Fresnel coefficients and modern mate-rials such as epsilon-near-zero films. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
CRIS-Team WoS Importer:2022-10-21